PERSEPSI ORANG TUA TENTANG PEMBERIAN VITAMIN A PADA ANAK DI TAMAN KANAK-KANAK - Afrika, Eka; Sundari, Winda; Sari, Ratna (JURNAL KESEHATAN TERAPAN, 2021)
Background: Vitamin A deficiency is a major health problem in developing countries, including Indonesia. Vitamin A deficiency mainly affects young children, among those who are deficient can experience xerophthalmia and eventually become blind, limited growth, weak body defenses, and increase the risk of death. This is evidence that vitamin A deficiency can continue from school age and adolescence to adulthood. Objective: To determine the positive and negative perceptions of parents about giving Vitamin A to children. Methods: This type of research is quantitative using a cross-sectional research design with a sampling technique using total screening obtained a sample of 78 respondents. Results: The results showed that the perceptions of mothers who had children under five about giving vitamin A were mostly positive, as many as 66 people (84.62%), and 12 people with negative attitudes (15.38%), most of the mothers' knowledge was also good ( 74.49%) regarding knowledge about giving vitamin A to children. Suggestion: health workers (doctors, midwives, nutrition cadres, and trained health workers) together with school principals and kindergarten teachers to further increase the knowledge of parents by means of more routine education and installing posters or pamphlets related to vitamin A for disease Vitamin A deficiency in toddlers can be avoided. Key words: Parents' Perception, Giving Vitamin A to Children